Design of Compact Tri-Band Fractal Antenna for RFID Readers - Mohamed Ihamji; Elhassane Abdelmounim; Hamid Bennis; Mostafa Hefnawi; Mohamed Latrach (Institute of Advanced Engineering and Science, 2017)
In this paper, a multiband and miniature rectangular microstrip antenna is designed and analyzed for Radio Frequency Identification (RFID) reader applications. The miniaturization is achieved using fractal technique and the physical parameters of the structure as well as its ground plane are optimized using CST Microwave Studio. The total area of the final structure is 71.6 x 94 mm2. The results show that the proposed antenna has good matching input impedance with a stable radiation pattern at 915 MHz, 2.45 GHz, and 5.8 GHz.